EVALUASI KOMPETENSI BERBICARA PADA MATA PELAJARAN BAHASA INDONESIA ANAK USIA DASAR - Rohmat Dwi Yunianta (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2023)
This article aimed to describe the types of language ability and skill evaluation tests, especially speaking skills in Indonesian language subjects for elementary school-age children. The writing of this article was carried out by means of literature study, namely collecting relevant information related to the topic that was the object of discussion. The background for this writing was because the portion for evaluating speaking competence in Indonesian language lessons at the elementary school level was still lacking. Evaluation in the field of elementary school Indonesian language lessons was more emphasized on aspects of reading and writing. Although in fact, language competence consists of at least 4 aspects, namely listening, reading, speaking and writing. The implementation and evaluation of learning Indonesian should refer to the fulfillment of the 4 competencies in a balanced portion and not be heavy on one of them. Evaluation of speaking competence could improve the quality of learning as a whole, both knowledge, concepts, values and the process of learning Indonesian in class. The form of speaking evaluation tests could be in the form of short talks based on pictures, interviews, retelling, free speech/speech, guided conversations, and discussions.